Human turbinate mesenchymal stromal cell sheets with bellows graft for rapid tracheal epithelial regeneration. (1st October 2015) - Park, Jeong Hun; Park, Ju Young; Nam, Inn-Chul; Hwang, Se-Hwan; Kim, Choung-Soo; Jung, Jin Woo; Jang, Jinah; Lee, Hyungseok; Choi, Yeongjin; Park, Sun Hwa; Kim, Sung Won; Cho, Dong-Woo
Graphical abstract: Abstract: Rapid functional epithelial regeneration on the luminal surface is essential when using artificial tracheal grafts to repair tracheal defects. In this study, we imposed human turbinate mesenchymal stromal cell (hTMSC) sheets for tracheal epithelial regeneration, and then assessed their potential as a new clinical cell source. In vitro, hTMSCs sheets showed high capacity to differentiate into tracheal epithelium. We fabricated a poly(ε-caprolactone) (PCL) tracheal graft by indirect three-dimensional (3D) printing technique and created a composite construct by transplanting the hTMSC sheets to its luminal surface of the tracheal graft, then applied this tissue-engineered tracheal graft to non-circumferential tracheal reconstruction in a rabbit model. 4 weeks after implantation, the luminal surface of tissue-engineered tracheal graft was covered by a mature and highly-ciliated epithelium, whereas tracheal grafts without hTMSC sheets were covered by only a thin, immature epithelium. Therefore, hTMSC sheets on the luminal surface of a tissue-engineered tracheal graft can accelerate the tracheal epithelial regeneration, and the tissue-engineered tracheal graft with hTMSC sheets provides a useful clinical alternative for tracheal epithelial regeneration.